Strategi Peningkatan Pendapatan Asli Daerah (PAD) Melalui Penggalian Potensi Ekonomi Daerah di Provinsi Kepulauan Riau - Noeridha, Neelam; Nadia, Nadia (Policy, Law and Political Research Center, 2023)
The strategic geographic location accompanied by the potential of great economic resources is a supporting factor for the Riau Islands economy. However, the advantage has not been utilized optimally by the Riau Islands Provincial Government. The low contribution of the original regional income (PAD) on APBD of the Riau Islands Province shows the high level of reference in the reference of the Riau Islands regard to the balance fund from the central government. The purpose of this study is to learn the strategy of the Government of Riau Islands Province to increase the original revenue, using the library study method of literature relating to the research issues. The results showed that the Riau Islands had a very abundant economic potential, so if ultimately utilized will have a positive impact on the increase in the original revenue (PAD). The Riau Islands Provincial Government needs to optimize the original revenue with the development of the economic potential of the Riau Islands by establishing local-based operating business (BUMD) based on local economic potential and focused on superior economic sectors and potential economic sectors to be developed.